Indications, materials and properties of 3D printing in dentistry: a literature overview (Research, Society and Development, 2020)
3D printing and digital manufacturing technologies have been largely used in dentistry in recent years and dentists and prosthetic technician are up to date and involved in the subject, following the advancement of technology. The objective of the present manuscript was to carry out a descriptive literature review, covering the processing methods, precision, types of materials used and the applications of 3D printing in dentistry. A bibliographic search was conducted in the PUBMED database (www.pubmed.gov), in which studies published from 2000 to 2020 were collected. Laboratory studies, case reports, systematic and literature reviews were included. Therefore, articles that did not address the topic in question, letters to the editor, opinion articles, duplicate literature and texts that were not in English were excluded. According to the inclusion and exclusion criteria, 75 research articles were selected. In dentistry the most common methods of 3D printing used are: stereolithography (SLA), material jetting (MJ), binder jetting, and Laser sintering. It is important to carefully consider the limitation of each method, material and operator’s skills in 3D printing for this technology to be more affordable in dentistry. Despite that, the accuracy of printing methods and materials used in different dental applications with 3D printing have been improving each day more, allowing a digital workflow with greater applicability and frequency of use in dentistry.